A Different Approach to the EGFR Inhibitor Gefitinib Involving Solid-Phase Synthesis - Sequeira, André; Lourenço, Ana; Ferreira, Luísa Maria; Branco, Paula Sério; Mendes, Zita; Lourenço, Nuno M. T.; Figueiredo, Margarida; Carvalho, Luísa C. R. (Synlett, 2018)
An efficient solid-phase synthesis approach is here reported for the first time to prepare the EGFR inhibitor Gefitinib. The five-step synthetic strategy used FMP resin as the solid support, and FTIR and colorimetric assays were used to track the reaction’s progress. Gefitinib was obtained with an overall yield of 40%.
Keywords: solid-phase synthesis; Gefitinib; quinazoline; FMP resin; colorimetric assays